MEDIAN LETHAL CONCENTRATION (LC50) TEST OF OIL BASE MUD (OBMs) ON TIGER PRAWN (Peneaus monodon Fab) - Jabarsyah, Abdul (Jurnal Harpodon Borneo, 2016)
This study was conducted to investigate toxicity of oil base mud (OBMs) use in oil drilling in various concentrationon marine living organism. Inorder to achieve the objectives of this study, acute toxicity tests were performed to clarified the median lethal concentration (LC50) of OBMs on tiger prawn (Peneaus monodon Fab.).The solid OMBs were obtained from oil drilling company and kept on cooling box under10oC. The toxicity test procedure used based on the standard methods for examination water or wastewater. The concentration of the test solutions were 10, 20, 35, 70, 135, 260,and 500 ppm. The 7000 post larvae (PL-25) of tiger prawn obtained from the PrawnHatchery and acclimatization for 10 days on amber aquariums before use for this toxicity test. Ten post larvae of tiger prawns each tank were used in four replicates on the sevenconcentrations of OBMs with one control. The lethal concentration LC50-96 using theprobit analysis.The mortality of prawn during the toxicity test for each concentration were 30%, 50%,60%, 70%, 80%, 100%, and 100% respectively and there was no mortality found on control. Using the Probit Method Analysis the lethal concentration value (LC50-96) of OBMs was 23,71 ppm. The LC50-96 was the concentration of the OBMs estimated to kill the post larvae of the tiger prawn exposed during 96 hours. Various symptoms and damages of were found on gill filaments, digestive organs, and hepatopancrease. Keywords: Oil Base Mud, Lethal Concentration (LC50-96), tiger prawn.